Treatment Adherence to Drug Therapyin Patients with Stable Coronary Artery Disease During the COVID-19 Pandemic - S. Y. Martsevich; Y. V. Lukina; E. D. Zharkova; N. P. Kutishenko (Рациональная фармакотерапия в кардиологии)
The new coronavirus infection (COVID-19) pandemic and the subsequent quarantine measures, particularly home isolation of the population, could have seriously affected the quality of pharmacotherapy and adherence to it by patients with chronic non-communicable diseases.Aim. To assess the dynamics of adherence to pharmacotherapy by patients with stable coronary artery disease (SCAD) in self-isolation during the COVID-19 pandemic.Material and methods. To accomplish the aim of the study, we selected 39 patients with SCAD who previously completed the ALIGN study, the purpose of which was to align patients’ medical therapies according to current clinical guidelines. From May 05, 2020, to May 14, 2020, a telephone survey was conducted of 39 patients with SCAD (37, 94.8%) males, mean age 67.6±8.5 years). After one year of participation in the ALIGN study, 87.1% of the patients were adherent to their prescribed pharmacotherapy. Adherence (overall and to specific medications) was assessed by means of the original adherence scale, which made it possible to identify violations in taking medications (non-adherence to the intake regime or discontinued intake of medications), and the main reasons for adherence violation were established. Adherence registered during the telephone survey at the time of the COVID-19 pandemic was compared to that obtained during the last time the patient participated in the ALIGN study.Results. During the period of home isolation, a substantial decline in the adherence of patients to pharmacotherapy was revealed. The percentage of adherent patients decreased from 87% to 54% due to an increase in the number of patients who stopped taking several or all of the recommended drugs during home isolation (p=0.024). The overall rate of adherence during the COVID-19 pandemic appeared to be even worse than before the start of the ALIGN study. A comparative analysis of subgroups with and without a decline in adherence revealed a trend suggesting that higher patient education (p=0.067) or previous percutaneous coronary intervention (p=0.063) can be considered a protective factor associated with fewer violations in adherence during the COVID-19 pandemic. Analysis of adherence to specific drugs showed that during self-isolation there was a decrease in adherence to antiplatelet drugs (p=0.047) and to statins (p=0.055). Adherence to beta-blockers, renin-angiotensin-aldosterone system inhibitors and dihydropyridine calcium antagonists remained unchanged.Conclusion. In patients with SCAD during the period of home isolation in the COVID-19 pandemic and associated difficulties in contacting the attending physician, there was a decline in adherence and an increase in the number of patients who stopped taking several or all prescribed drugs.